Flight patterns [large type] - White, Karen (Karen S.) (Wheeler Publishing Large Print, 2016)
Georgia Chambers sifts through other people's pasts while trying to forget her own. Then her work as a fine china expert sends her to the place she swore she'd never revisit. To embrace her own life -- mistakes and all -- she'll have to find the courage to confront the ghosts of her past.